The Effect of Spiritual Emotional Freedom Technique and Music Therapy on Reducing Anxiety in Cardiovascular Patients in the Emergency Department - Ahmad Muzaki; Mugihartadi Mugihartadi; Windra Bangun Sucipto; Bimo Saputro (Indonesian Journal of Global Health Research, 2024)
Patients and crowded procedures have the potential to increase discomfort and cause patient anxiety in the emergency room. SEFT therapy is a spiritual therapy that can reduce anxiety without risk. The development of music therapy has a therapeutic effect in overcoming anxiety disorders. Objective: This study aims to determine the effect of SEFT therapy and music therapy on reducing anxiety in cardiovascular patients in the emergency room at Prembun Regional Hospital. Method: The design in this research uses a pre-experiment with a one group pre-post test design approach. The total sample of 25 people was taken using purposive sampling technique. The data analysis used was a paired sample t-test. Results: Cardiovascular patient anxiety before being given SEFT therapy and music therapy was in the category of moderate anxiety disorder (40.0%). Most of the patient anxiety after being given SEFT therapy and music therapy was at a non-anxious level, namely 14 people (56%). Conclusion: Based on the results of the study, it was found that there was a decrease in the level of anxiety in patients after being given SEFT therapy and music therapy with a p-value of 0.000.